An Empirical Study of Formal Procedure Specification. - Bell, D. A. (Contemporary Educational Psychology, 1978)
Programming a computer is a problem-solving activity which can be categorized as formal procedure specification. It is a useful vehicle for the study of this aspect of problem-solving because the procedures can be automatically tested for correctness. The reported study focuses on the incidence and severity of errors committed during program development by novice programmers. The observations are summarized in tabular form, to permit insights into the sorts of errors virtually untrained students make when specifying procedures, and the problems they have eliminating them.